THE EFFECTIVENESS OF DIGITAL RECRUITMENT STRATEGIES ON CANDIDATE QUALITY AND EMPLOYEE RETENTION LEVEL AT PT XYZ - Yusup Erisyadi; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effectiveness of the digital recruitment strategy implemented by PT XYZ in improving candidate quality and employee retention rates. The research method uses a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats of the company's digital recruitment strategy. The results show that the use of digital platforms, such as applicant tracking systems (ATS), social media, and AI in the recruitment process, can increase the reach of qualified candidates by up to 25%, accelerate the recruitment process, and reduce operational costs. In addition, this strategy also has a positive impact on employee retention through more accurate selection and a better candidate experience during the recruitment process. However, limitations such as the need for technology training and resistance to change are challenges that must be overcome. This study provides practical recommendations for optimizing digital recruitment strategies to support the sustainability of quality human resources in the company.